(untitled) (London Journal of Medical and Health Research, 2026)
Introduction: The practice of cardiology in fragmented healthcare systems faces increasing structural pressures related to heavy workloads, inadequate compensation, and limited professional recognition. These factors negatively affect physician well-being, contribute to burnout, and pose challenges to workforce sustainability. In parallel, demographic changes characterized by the aging specialist population and the reduced influx of young physicians are generating concern regarding the future availability of qualified cardiovascular professionals. Objective: The aim of this study was to evaluate cardiologists’ perceptions of working conditions, income satisfaction, professional recognition, training pathways, and future career expectations, as well as to explore their association with demographic and occupational characteristics. Methods: An observational, analytical, cross-sectional study was conducted using an anonymous, self-administered survey distributed nationwide between June and September 2023. The questionnaire, validated by an institutional ethics committee, consisted of 16 items grouped into three domains: relationship with scientific societies, professional recognition, working conditions, and continuing medical education. Demographic and occupational variables were also collected. Data analysis was performed with descriptive statistics and Pearson or Spearman correlation coefficient analysis, as appropriate, using Python 3.1. Results: A total of 404 responses were analyzed, predominantly from more experienced cardiologists, reflecting an aging workforce. Younger professionals reported a heavier weekly workload, with a significant inverse correlation observed between age and hours worked (r = −0.41). Economic dissatisfaction was highly prevalent: over 70% of respondents expressed dissatisfaction with their income, and 95% felt that their remuneration did not adequately reflect their workload. Nearly half anticipated a worse economic situation within the next five years. Satisfaction with current income showed a positive correlation with future economic expectations (r = 0.23). Medical residency remained the preferred training pathway, while support for professional recertification was moderate and positively associated with greater economic satisfaction. Conclusions: The practice of cardiology in fragmented healthcare systems is characterized by excessive workload, widespread economic dissatisfaction, and unfavorable future prospects, particularly among younger professionals. These conditions contribute to professional burnout and threaten workforce retention and generational renewal. It is essential to implement comprehensive health policies that address remuneration models, professional recognition, training structures, and physician well-being to ensure long-term sustainability of cardiovascular care in diverse healthcare settings.